Methodological process to plan and implement an educational Campaign to increase bean consumption. - Rodríguez, Ligia; Rodríguez, Shirley (Agronomía Mesoamericana, 2004)
This article describes planning of an educational Campaign to increase bean consumption, and the activities carried out during its implementation. At the same time, it highlights the contributions of an initial assessment and the result of the final evaluation. Finally, the article summarizes the “lessons learned” during implementation of these two phases, and provides considerations about their importance and applicability. Other “lessons learned” throughout the process are also included.